21 December, 16:01
Which equation is equivalent to the equation below?
5 (n + 6 = 2 (n-3) + 4
F. 5n + 6=2n + 1
G. 5n + 6 = 2n - 2
H. 5n + 30 = 2n + 1
I. 5n + 30 = 2n - 2
21 December, 16:39
The answer you are looking for is the letter i.
5n + 30 = 2n - 2
Know the Answer?
New Questions in Mathematics
According to the income effect, when the price of automobiles rises, people buy fewer automobiles because a. the nominal amount of their paychecks is smaller. b. the purchasing power of their income is reduced. c.
What category of criminal act would a driver who received a speeding ticket be classified as? a. petty offense c. felony b. misdemeanor d. civil
Is the sequence 3,12,36, a geometric sequence? explain
What is 1/3 added to 1/4
The formula for the nth term of an arithmetic sequence can be found using the formula an=a1 + (n-1) d. Which of the following is equivalent to this equation? A) n=an+a1 B) n=an+a1-d/d C) n=an-a1 D) n=an-a1+d/d
» Which equation is equivalent to the equation below? 5 (n + 6 = 2 (n-3) + 4 F. 5n + 6=2n + 1 G. 5n + 6 = 2n - 2 H. 5n + 30 = 2n + 1 I. 5n + 30 = 2n - 2